2007
DOI: 10.1007/s12010-007-8057-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-controlled Biosurfactant Production in a Bench Scale Bioreactor

Abstract: Rhamnolipids have been pointed out as promising biosurfactants. The most studied microorganisms for the aerobic production of these molecules are the bacteria of the genus Pseudomonas. The aim of this work was to produce a rhamnolipid-type biosurfactant in a bench-scale bioreactor by one strain of Pseudomonas aeruginosa isolated from oil environments. To study the microorganism growth and production dependency on oxygen, a nondispersive oxygenation device was developed, and a programmable logic controller (PLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…This is consistent with the results described by Yeh et al [17] and Amaral et al [3] who have mentioned that biosurfactant production rose with the increase of agitation speed. Kronemberger et al [18] have shown that a rhamnolipid production by Pseudomonas aeruginosa depend on the specific oxygen uptake rate. The agitation speed affects the mass transfer efficiency of both oxygen molecules and medium components.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results described by Yeh et al [17] and Amaral et al [3] who have mentioned that biosurfactant production rose with the increase of agitation speed. Kronemberger et al [18] have shown that a rhamnolipid production by Pseudomonas aeruginosa depend on the specific oxygen uptake rate. The agitation speed affects the mass transfer efficiency of both oxygen molecules and medium components.…”
Section: Discussionmentioning
confidence: 99%
“…They were then incubated at 30˚C at 170 rpm for 168 hours. Every 24 hours, 1.5 mL aliquots were taken for analysis of cell growth and rhamnolipid concentration [16] [17].…”
Section: Rhamnolipid Productionmentioning
confidence: 99%
“…Rhamnolipid purification was carried out by extraction, using a chloroform/methanol/culture medium mixture, in the proportion of 2:1:1 and a separating funnel (see Figure 1). The organic chloroform rich phase was separated, the solvent evaporated a pasty product with a brownish color [17] was obtained.…”
Section: Rhamnolipid Extractionmentioning
confidence: 99%
“…Important variables are carbon and nitrogen sources (Santos et al, 2002), also the use of glucose as a sole carbon source enhances the production of high yield of Biosurfactants (Fooladi et al .2013). Potential nutrient limitations and other physical and chemical parameters such as oxygen (Kronemberger et al, 2008), temperature and pH (Mukherjee et al, 2006) were considered. Bacillus licheniformis is 7 after incubation for 10 days.…”
Section: Growth On Macconkey Agar Mediummentioning
confidence: 99%